Understanding Provider-Level Variation in Clinical PracticeTake-Home Points - Kanupriya Soni, MD; Leigh A. Bukowski, MPH; Billie S. Davis, PhD; Joel M. Levin, BA; Jeremy M. Kahn, MD (CHEST Critical Care)
Background: Clinician practice patterns vary widely in the ICU, particularly in the context of therapies with moderate-quality evidence. A better understanding of the psychological factors underlying provider-level practice variation may reveal targets to standardize practice and speed adoption of new evidence. Research Question: Are provider-level psychological traits associated with practice patterns in the ICU? Study Design and Methods: We administered a longitudinal questionnaire to intensivist clinicians in a single integrated health system from 2018 through 2021. We selected corticosteroids in septic shock as an example of a guideline-recommended practice supported by moderate-quality evidence. In response to a clinical vignette of septic shock, intensivists rated their willingness to administer corticosteroids, their perceptions of the strength of evidence, and their perception of how well the mechanism of action is understood. Via the same questionnaire, we measured psychological traits hypothesized to affect decision-making under uncertainty. We used multivariate regression to examine the relationship between these factors and respondents’ willingness to treat with corticosteroids. Results: The overall survey completion rate was 50.5%. Among 201 participants, 101 participants (50%) were attending physicians, 77 participants (38%) were fellow physicians, and 23 participants (11%) were advanced practice providers. Willingness to treat with corticosteroids increased over time, from 15.3% to 24.4% in 2021. In multivariate regression analyses using generalized estimating equations for repeated measures, risk tolerance (OR, 1.34, 95% CI, 1.07-1.67; P = .01) and perceived strength of evidence (OR, 1.45; 95% CI, 1.18-1.77; P < .001) were associated with increased willingness to treat with corticosteroids, controlling for other factors. Willingness to treat was not associated with perceived understanding of the mechanism of action or other psychological factors. Interpretation: Our findings indicate that ICU providers’ individual level of risk tolerance is associated with their willingness to prescribe corticosteroids for septic shock.